Development of Audiovisual Learning Media on Electrolyte and Non-Electrolyte Chemistry Topic With Powtoon Application - Anis Muyassaroh; Ivan Ashif Ardhana (Pusdiklat Tenaga Teknis Pendidikan dan Keagamaan, 2022)
Aim of this research is to explore validity and students’ response to learning media with powtoon on electrolyte and non-electrolyte topic. Research method is 4D development with define, design, develop dan disseminate process. Nevertheless, this research only toward develop step because of time limiting. This research uses the instruments of interview and content and media validity. Data analysis shows analyze qualitative data from interview result and quantitative data form students’ response questionnaire by calculate this average. Content validity result shows average of 90% on well category. Media validity result shows average of 95,7% on well category too. Students’ response on small scale test shows average of 82,08% on well category. Based on these results, learning media valid to be used as learning media also could be use to support development of similar media on another research.